Management of meniscal and articular cartilage injuries in elite level tennis players - Branche, G. C. (2001)
Tennis players are predisposed to overuse injuries, which can involve damage to the articular cartilage and the menisci. About the types of common injuries and the rehabilitation for tennis players.